UNEP's Role in Overcoming Climate Disasters as a Threat to Human Rights in Asia Pacific 2020-2021 - Evita Fitria Sukma; Okta Wahyudi; Razeta Zahra (Social Issues Quarterly, 2022)
The issue of climate change is a strategic issue in the study of international relations. How not, the impacts caused by climate change, especially extreme climate change, not only have an impact on the environment, but also human rights. At least the rights to life, to obtain food and shelter are also threatened. This is certainly a concern of the global community. Therefore, this study aims to find out what is the role of the United Nations of Environment Program (UNEP) as an international organization engaged in the environment in overcoming this problem. This study uses a qualitative approach with secondary data types from previous studies. The data analysis technique used is descriptive qualitative method. Based on the research results, in dealing with the impacts of climate change, UNEP emphasizes cooperation with various parties, such as the Office for the Coordination of Humanitarian Affairs (OCHA) and the European Union (EU). In addition, UNEP also empowers communities directly affected by climate change.